Measuring deming management model in the context of sports tourism organizations - Rodrigues, Pedro M. (2011)
Concepts related to service’s quality have not evolved in the same way as those related to industries. Nevertheless, total quality management’s theoretical basis and methods allow its use in both sectors. This study is an application of the Deming Management Model, developed by Anderson et al (1994), to the context of sports tourism industry. The referred method sustains that leadership efforts aiming at the simultaneous creation of a cooperative and learning organization facilitate the implementation of processmanagement practices. These, when implemented, support customer satisfaction and organizational survival through sustained employee fulfilment and continuous improvement of processes, products, and services (Anderson, et al., 1994). Previous studies support it’s applicability in manufacturing (Rungtusanatham et al., 1998) and services (Douglas & Fredendall, 2004; Fisher et al., 2005). Despite the existence of worldwide practical evidence that proves the model’s effectiveness (Rungtusanatham et al., 2005), the fact is that empirical research is still scarce. Therefore, the following goals have been set: a) corroborate Deming’s model applicability, proposed by Anderson et al. (1994) to sport tourism industry; b) develop and verify the applicability of the proposed measurement model. After analyzing the existing literature on the development of scales related to TQM practices, it was clear that the concepts underlying the model proposed by Anderson et al. (1994) would be better operationalized by using scales which had been previously published. Hence, they were translated and adapted to the context. The empirical analysis was structured in two studies: expert’s validation, pre-test, exploratory factor analysis and confirmatory factor analysis.